1995
DOI: 10.1101/lm.2.2.81
|View full text |Cite
|
Sign up to set email alerts
|

A critical period of protein kinase activity after tetanic stimulation is required for the induction of long-term potentiation.

Abstract: A critical period of protein kinase activity required for the induction of long-term potentiation (LTP) was determined in area CA1 of hippocampal slices using the broad-range and potent protein kinase inhibitors K-252a and staurosporine. As reported previously, K-252a and staurosporine blocked LTP induction when applied before, during, and after high-frequency stimulation (HFS). In contrast, K-252a did not block LTP when applied only before and during HFS and washed out immediately after HFS. K-252a and stauro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 75 publications
1
13
1
Order By: Relevance
“…This suggests that the molecular mechanisms bidirectionally regulating synaptic transmission involve a constitutively active PKC, perhaps PKM, although there may be other forms of autonomous PKC to be characterized in future studies. In addition, however, staurosporine and its analog K252a, inhibitors acting on the catalytic domain of many kinases, including conventional PKCs and CaM-kinase II (Ward and O'Brian, 1992;Huber et al, 1995), have been reported not to reverse LTP maintenance (Denny et al, 1990b;Muller et al, 1992; Huber et al, 1995) (but see Matthies et al, 1991). These results appear to contradict the experiments with H7 and chelerythrine.…”
Section: Bidirectional Regulation Of Autonomous Pkc In the Maintenanccontrasting
confidence: 56%
See 1 more Smart Citation
“…This suggests that the molecular mechanisms bidirectionally regulating synaptic transmission involve a constitutively active PKC, perhaps PKM, although there may be other forms of autonomous PKC to be characterized in future studies. In addition, however, staurosporine and its analog K252a, inhibitors acting on the catalytic domain of many kinases, including conventional PKCs and CaM-kinase II (Ward and O'Brian, 1992;Huber et al, 1995), have been reported not to reverse LTP maintenance (Denny et al, 1990b;Muller et al, 1992; Huber et al, 1995) (but see Matthies et al, 1991). These results appear to contradict the experiments with H7 and chelerythrine.…”
Section: Bidirectional Regulation Of Autonomous Pkc In the Maintenanccontrasting
confidence: 56%
“…PKC␥ was decreased only in LTD slices (57.1 Ϯ 4.1, p Ͻ 0.05), but not in slices receiving 3 and 100 Hz (108.9 Ϯ 7.0). several protein kinases, CaM-kinase II (Lisman, 1994), full-length PKCs , cGMP-dependent kinase (Zhuo et al, 1994), cAMP-dependent kinase (Huang and Kandel, 1994;Blitzer et al, 1995), and tyrosine kinases (O'Dell et al, 1991), all appear to act interdependently (Huber et al, 1995;Wang and Kelly, 1995), so that the inhibition of any single pathway prevents LTP. On the other hand, calcineurin has been implicated in the induction mechanisms of LTD (Mulkey et al, 1994).…”
Section: Pkm and The Divergence And Convergence Of Signal Transductiomentioning
confidence: 99%
“…One could argue that CaN-inhibited synaptic potentiation only results from basal CaM-KII / PKC activities (Ocorr and Schulman, 1991;Huber, 1995) instead of from an absolute increase in their activities by positive feedback. Because inhibiting postsynaptic CaM-KII / PKC activities does not significantly alter basal synaptic transmission (Tsien et al, 1990;Feng and Wang, 1992;Wang and Kelly, 1996), basal CaM-KII / PKC activities are not high enough to strengthen synaptic transmission.…”
Section: Discussionmentioning
confidence: 99%
“…It may be simply understood as shifting the balance between protein kinase and phosphatase activities toward enhancing the phosphorylation of protein substrates responsible for synaptic transmission without increasing the absolute activity of protein kinases. In other words, after CaN is inhibited, the action of basal kinase activities on synaptic substrates becomes dominant, because Ca 2ϩ -dependent protein kinases are active under basal conditions in hippocampal slices (Ocorr and Schulman, 1991;Huber, 1995). However, the inhibition of postsynaptic CaM-KII and PKC activities do not significantly alter basal synaptic transmission (Tsien et al, 1990;Feng and Wang, 1992;Wang and Kelly, 1996a), implying that basal CaM-KII and PKC activities are below a threshold for strengthening synaptic transmission.…”
mentioning
confidence: 99%
“…Hippocampal LTP consists of several, partly overlapping phases involving different molecular pathways. Besides being sensitive to kinase inhibitors (Huber et al, 1995), the initial phase is dependent on GluA1 function, as genetically modified mice lacking the GluA1 subunit (Gria1 À/À mice) show impairment of the initial phase of LTP (Romberg et al, 2009). Moreover, an allosteric positive AMPA receptor modulator was reported to enhance approximately the first 10 min of LTP in vivo (Bernard et al, 2010), similar to our results with 10 lM Tianeptine.…”
Section: Discussionmentioning
confidence: 99%